Effects of abiotic stresses on the expression of chitinase-like genes in Acyrthosiphon pisum - Li, Chunchun; Ul Haq, Inzamam; Khurshid, Aroosa; Tao, Yan; Quandahor, Peter; Zhou, Jing-Jiang; Liu, Chang-Zhong (Frontiers in Physiology, 2022)
Insect chitinases play a crucial part to digest chitin in in the exoskeleton during the molting process. However, research in insect that relates insect chitinase to environmental stress response is very limited. This study was the first conducted to expression analysis of chitinase- related genes in A. pisum under abiotic stress. Here, we identified five chitinase-like proteins (ApIDGF, ApCht3, ApCht7, ApCht10 and ApENGase), and clustered into five groups (group II, III, V, Ⅹ and ENGase). Developmental expression analysis revealed that the five A. pisum chitinase-related genes were expressed at whole developmental stages with different relative expression patterns. When aphids were exposed to various abiotic stresses including temperature, insecticide and the stress 20-hydroxyecdysone (20E) and differentially expressed of all 5 chitinase genes in A. pisum. The results showed that insecticide such as imidacloprid down-regulated the expression of these five Cht-related genes. Analysis of temperature stress of A. pisum chitinase suggested that ApCht7 expression was high at 10 ºC, which demonstrates its important role in pea aphid under low temperature. Conversely, ApCht10 was more active under high temperature stress, as it was significantly up-regulated at 30 ºC. Besides, 20E enhanced ApCht3 and ApCht10 expression in A. pisum, but reduced ApCht7 expression. These findings provide basic information and insights for the study of the role of these genes under abiotic stress, which advances our knowledge in the management of pea aphids under multiple stresses.